PERANCANGAN UI MOBILE APPS “LORA” UNTUK MEMBANTU PROGRAM DIET PENGGUNA REMAJA HINGGA DEWASA DI INDONESIA - Jayanti, Hana; Nirwana, Aditya; Prasetya, Bintang Pramudya Putra (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2025)
The prevalence of obesity and overweight in Indonesia continues to rise, particularly among adolescents and adults. Unhealthy lifestyles and a lack of awareness regarding calorie intake management are among the main contributing factors. In response to this issue, this study aims to design the user interface (UI) of a mobile application called LORA, which serves as a supportive tool for diet programs by providing informative, interactive, and user-friendly features. This research adopts a descriptive qualitative method using the Design Thinking approach, which consists of five stages: empathize, define, ideate, prototype, and test. Data were collected through competitor analysis, user questionnaires, and user testing sessions involving an interactive prototype. The testing results indicate that most respondents found the interface easy to understand, visually appealing, and helpful in tracking their daily calorie intake. Based on these findings, it can be concluded that the UI design of the LORA application fulfills both functional and aesthetic user needs and holds potential as a digital solution to promote healthy lifestyle changes among adolescents and adults in Indonesia.